Analisis Kinerja Sistem Proteksi Arus Lebih Pada PT. Sri Intan Karplas Industry - Fajar Ahmad; Zuraidah Tharo; Dikcy Lesmana (Jurnal Nasional Teknologi Komputer, 2025)
This research explains the positive impact of the overcurrent relay (OCR) protection system, which functions to protect against excessive currents at PT. Sri Intan Karplas Industri. Overcurrent protection is the primary means of keeping equipment safe from problems such as short circuits and overloads. This research was conducted by observing specific situations and collecting field data, including test data and calculations on the MCGG82 OCR. Testing showed that the OCR relay was still suitable for use because the difference between the tripping time during testing and the calculated time was within 5%. This research also demonstrated that the OCR system is excellent at protecting against excessive currents, which can help protect electrical power systems in industrial environments.